Supply Chain Risk Analysis on Koi Fish Cultivation Business in Sumberdodol Village, Panekan District, Magetan Regency - Buyung Purnomo Waluyo; R. Sugeng Rahardjo; Jefri Putri Nugraha (PT FORMOSA CENDEKIA GLOBAL, 2023)
Indonesia has various sectors that make an important contribution to its development, one of which is the fishing industry. Koi fish is a type of fish that is cultivated in Indonesia. Risk management is important for controlling risks that may occur by identifying risks and risk causes, risk categories and possible risk responses. Risk management is carried out to reduce the possibility of risk impact on this project. The House of Risk (HOR) method is used to identify risk events and risk agents and design mitigation to address the causes of these risks. This study identified 10 risk events and 16 risk drivers through the project. The priority risks addressed are A1 (ineffective financial management) and A7 (long-term material shortage) with 4 recommended mitigation actions.